Pengaruh Literasi Akuntansi Dan Pemasaran Online Terhadap Keberhasilan Usaha Bagi Pelaku UMKM - Ashar Basyir; Ghina Kemala Dewi; Wigiyanti (Forum Kerjasama Pendidikan Tinggi, 2024)
Accounting literacy is the understanding of transactions that require management to make critical accounting considerations, explain financial transactions, make decisions, and justify why decisions are made as well as the consequences of management decisions. This study aims to determine the influence of applying accounting literacy and online marketing on business success and the challenges faced by SMEs (Micro, Small, and Medium Enterprises). The independent variables used in this study are accounting literacy and online marketing, while business success is the dependent variable. The sample used in this research was obtained using saturation sampling method, where all members of the entire population were used as samples. The analytical technique used in this study is multiple linear regression analysis and hypothesis testing using SPSS software v.23. The results of this study indicate that the application of accounting literacy yielded a partial t-test result with a calculated t-value of 0.880 < tabular t-value of 2.052 with a significance level of 0.387 > 0.05, thus it can be concluded that H1 is rejected which means there is no influence of Accounting Literacy on Business Success. Online marketing yielded a partial t-test result with a calculated t-value of 3.022 > 2.052 and a significance value of 0.005 < 0.05, meaning H2 is accepted which means there is an influence of Online Marketing on SME Business Success in Caringin Village. Simultaneous testing (F test) of the third hypothesis, which is that accounting literacy and online marketing influence business success, showed a significance value of 0.000 < 0.05 and an F-value of 13.119 > tabular F-value of 3.34. This indicates that both accounting literacy and online marketing variables simultaneously influence business success. This can improve financial management of SMEs, facilitate SMEs in obtaining funding, expand market reach, improve cost efficiency of SME promotion, and enhance profitability and competitiveness of SMEs.